2018
DOI: 10.3390/su10124599
|View full text |Cite
|
Sign up to set email alerts
|

Noise Indicators for Size Distributions of Airborne Particles and Traffic Activities in Urban Areas

Abstract: The aim of this study was to explore the relationships among the particle number concentration (PNC), noise, and traffic conditions. Field measurements were conducted to measure the temporal variabilities of the noise levels and PNC over 24 h in a location adjacent to three main traffic roads in Seoul, Korea. The PNC was measured in the range of 0.3 to 10 µm. The noise data was measured by utilizing both the overall levels and spectral characteristics. Traffic data including volumes and speeds of vehicles on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Moreover, the fast growth of demand for transport services, in terms of both passenger and cargo flows, has a direct effect on the number of road accidents and their outcomes [28][29][30], increased noise and vibrations [31,32], uncontrolled land consumption [33,34], and residents' life quality. A major problem in that respect is that internal combustion engine vehicles (ICEVs) still dominate the transport services market, and transport remains very dependent on oil-oil-derived fuels account for 95% of energy consumption in transport [35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the fast growth of demand for transport services, in terms of both passenger and cargo flows, has a direct effect on the number of road accidents and their outcomes [28][29][30], increased noise and vibrations [31,32], uncontrolled land consumption [33,34], and residents' life quality. A major problem in that respect is that internal combustion engine vehicles (ICEVs) still dominate the transport services market, and transport remains very dependent on oil-oil-derived fuels account for 95% of energy consumption in transport [35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, transport that is indispensable for people is becoming a bigger threat to their health and life, as well as to the surrounding environment. The dynamic increase in demand for transport services translates into traffic congestion [6,7], an increase in road accidents, land consumption [8,9], as well as increase in noise and vibration [10,11]. The growing demand for transport services also increases fuel consumption.…”
Section: Sustainable Transport Development Pursuant To Eu Policy -Literature Reviewmentioning
confidence: 99%
“…With rapid urbanization and motorization of travel in cities over the past few decades, various environmental issues have emerged that largely affect urban livability and environmental sustainability, especially in the city centers where human activities and mobility usually concentrate. Evidence has shown that traffic noise and urban heat islands are two of the key factors contributing to the decline in life quality and the overall well-being of residents and that such negative effects are the strongest in dense and congested city centers [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%